(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda is the science of living beings. The main objective of Ayurveda is to protect the health of the healthy and to alleviate the disorders in the diseased. In Ayurveda, two types of the substratum of diseases are discussed i.e., Shareera and Manas. Ayurvedic definition of Swastha emphasizes on physical, psychological, and spiritual well being which is similar to the definition of WHO as health is a state of complete physical, mental and not just the absence of disease, but also social well-being. So, both the Ayurveda and Modern science says that physical health, as well as mental health, should be considered, then only a person can live a healthy life. Health is not only a goal in itself but, perhaps more importantly, the means by which one can achieve longevity. Many principles and methods for the prevention of mental health and cure of mental disorders are given in Ayurveda. One of them is the concept of Trivarga i.e., Dharma, Artha and Kama which is being discussed in the research paper. Therefore, in this article we are trying to draw a concept of “Trivarga” which may be helpful for the researcher and physician in management of Manas roga.